Systematic review and meta-analysis: de novo combination of nucleos(t)ide analogs and pegylated interferon alpha versus pegylated interferon alpha monotherapy for the functional cure of chronic hepatitis B - Wei, Na; Zheng, Bin; Cai, Hongfu; Li, Na; Yang, Jing; Liu, Maobai (Frontiers in Pharmacology, 2024)
Optimizing antiviral treatment strategies could improve the functional cure (FC) rate of patients with chronic hepatitis B (CHB). This study aims to systematically review the FC rate of the de novo combination of nucleos(t)ide analogs (NAs) and pegylated interferon α (PEG-IFNα) versus that of PEG-IFNα monotherapy for CHB.Methods: Databases were searched until December 31, 2023. Selected studies included randomized controlled trials on the de novo combination of NAs and PEG-IFNα versus PEG-IFNα monotherapy for 48 weeks in patients with CHB to achieve FC, which was defined as hepatitis B surface antigen (HBsAg) loss and/or HBsAg seroconversion. Meta-analysis was conducted in accordance with the efficacy at the end of treatment and different time points during follow-up.Results: A total of 10 studies, encompassing 2339 patients in total, were included. Subgroup analysis was conducted in accordance with whether first-line NAs were used. It found no statistically significant difference between HBsAg loss and HBsAg seroconversion at the end of treatment. Serum HBV DNA < 500 copies/ml significantly differed between the two groups at the end of treatment and did not significantly differ during follow-up. Meanwhile, HBsAg loss and HBsAg seroconversion showed statistically significant differences at 24 weeks of follow-up.By contrast, no statistically significant difference was found in HBsAg loss at 48 weeks of follow-up.Without distinguishing the eligible preponderant population, the efficacy of the de novo combination of NAs and PEG-IFNα in treating patients with CHB was not superior to that of PEG-IFNα monotherapy.